(untitled) (Communications in Mathematical Research, 2021)
We characterize the boundedness and compactness of weighted composition operators among some Fock-Sobolev spaces. We also estimate the norm and essential norm of these operators. Furthermore, we discuss the duality spaces of Fock-Sobolev spaces F^p,m_s when 0 < p < ∞.